Effects of platelet-rich fibrin produced by three centrifugation protocols on bone neoformation in defects created in rat calvaria - de Souza Ferreira Sávio, Débora; da Silva, Lucia Moitrel Pequeno; Reis, Gabriel Guerra David; Denardi, Ricardo Junior; da Costa, Natacha Malu Miranda; Furlaneto, Flávia Aparecida Chaves; de Souza, Sérgio Luís Scombatti; de Almeida Barros Mourão, Carlos Fernando; Miron, Richard J.; Okamoto, Roberta [UNESP]; Messora, Michel Reis (Taylor & Francis, 2023)
This study evaluated the potential of Leukocyte-platelet-rich fibrin (L-PRF; fixed angle centrifugation protocol), Advanced-platelet-rich fibrin (A-PRF; low-speed fixed angle centrifugation protocol), and Horizontal-platelet-rich fibrin (H-PRF; horizontal centrifugation protocol) in bone neoformation in critical size defects (CSDs) in rat calvaria. Thirty-two rats were divided into groups: Control (C), L-PRF, A-PRF, and H-PRF. 5 mm diameter CSDs were created in the animals' calvaria. Defects from group Control (C) were filled with blood clots, while defects from groups L-PRF, A-PRF, and H-PRF were filled with respective platelet-rich fibrin (PRF) membranes. L-PRF, A-PRF, and H-PRF were prepared from animal blood collection and specific centrifugation protocols. At 14 and 30 days, calcein (CA) and alizarin (AL) injections were performed, respectively. Animals were euthanized at 35 days. Microtomographic, laser confocal microscopy, and histomorphometric analyzes were performed. Data were statistically analyzed (ANOVA, Tukey, p < .05). L-PRF, A-PRF, and H-PRF groups showed higher values of bone volume (BV), newly formed bone area (NFBA), and precipitation of CA and AL than the C group (p < .05). The H-PRF group showed higher values of BV, number of trabeculae (Tb. N), NFBA, and higher precipitation of AL than the A-PRF and L-PRF groups (p < .05). Therefore, it can be concluded that: i) L-PRF, A-PRF, and H-PRF potentiate bone neoformation in CSDs in rat calvaria; ii) H-PRF demonstrated more biological potential for bone healing.